A wide split, cryocooler refrigerated high temperature superconducting magnet, for industrial coating applications - Hales, P; Hickman, A; Cooke, K; Teer, D; Jones, H (2008)
We present a description of the design, construction and operation of a magnet system comprising of 2 HTS coils separated by 164 mm, that can encompass a plasma coating module. The coil system comprises of two winding packages of 3 Pancake pairs of BSCCO (Bismuth Strontium Calcium Copper Oxide)/Ag tape. These are mounted such that they are in optimum thermal contact with an Edwards Coolstar Coldhead, model 6/30, which is attached to a Cryodrive 3.0 compressor unit. This allows operation of the magnets down to 20 K. The windings provide superconducting ampere turns for an iron core. The main objective of this project is to explore the replacement of high energy density permanent magnets with electromagnets in order (a) to achieve higher fields and (b) to be able to vary the field in time during a given coating process.